A Response Surface Methodology for Styrene Degradation Using Fenton’s/UV-Fenton’s Oxidation - Yoswathana, Nuttawan (Asian Journal of Chemistry, 2012)
Styrene is one of hazardous wastes sites that purposed on the EPA National Priorities List. Fenton’s and UV-Fenton’s oxidation for the styrene degradation were investigated by a response surface methodology using central composite Box-Behnken design as a tool for optimization in term of % COD removal. The technical scientific feasibility method was assessed by Fenton’s oxidation found that the optimum molar ratio as [H2O2]:[FeSO4]: [styrene (C8H8)] was [20]:[1.81]:[1], the COD removal 92.67 % at 30 ºC for reaction time 45 min and the reaction rate was zero order with kinetic rate constant of 0.018 mM/min. A response surface methodology was to applied to optimize the Fenton’s oxidation conditions: the molar ratio of [H2O2]:[Fe2+]:[C8H8] was [22.73]:[1.81]:[1.06] at 30 ºC, reaction time 42.12 min and the COD removal was 94.90%. In UV-Fenton’s oxidation with UV 80 watt, the optimum molar ratio of [H2O2]:[Fe2+]:[C8H8] was [22.54]:[1.81]:[1.04] at 30 ºC for reaction time 29.89 min and the COD removal was 95.03 %. Under these conditions, it was possible to obtain the maximum styrene degradation using optimization from response surface methodology of Fenton’s/UVFenton’s oxidation.